P120 inhibits LPS/TNFα-induced endothelial Ang2 synthesis and release in an NF-κB independent fashion. (November 2019) - Li, Ranran; Liu, Yiyun; Li, Lei; Zhang, Ruyuan; Tang, Yaoqing
Highlights: p120 inhibits LPS/TNFα-induced endothelial Ang2 synthesis and release. p120-mediated repression of Ang2 is in an NF-κB independent manner. Transcription factor Ets1 mediates LPS/TNFα-induced Ang2 expression. p120 inhibits LPS/TNFα-induced upregulation of Ets1. Abstract: Adherens junction protein p120 is thought to be crucial for maintaining vascular integrity, which is important in many pathologies and diseases including atherosclerosis, vascular malformations, hemorrhagic stroke, sepsis and others. However, the mechanisms responsible for this is not completely understood. In this study, using an unbiased proteomics approach, followed by other experimental techniques, we identified that in HUVECs p120 overexpression inhibits LPS/TNFα-induced angiopoietin-2 (Ang2) expression, a key switch of endothelial destabilization. Interestingly, p120 overexpression did not inhibit LPS/TNFα-induced expression of adhesion molecules/cytokines including VCAM-1, ICAM-1, E-selectin, MCP-1, IL-8 and IL-6 in our experimental system. Furthermore, this p120-mediated repression of Ang2 is in an NF-κB independent manner, possibly via transcription factor Ets1. Our results demonstrate that p120 influences vascular integrity by secreted signals, providing new insights into the mechanisms of p120-mediated vascular stability.